Detection limit of Mycobacterium chimaera in water samples for monitoring medical device safety: insights from a pilot experimental series. Issue 3 (July 2018) - Schreiber, P.W.; Köhler, N.; Cervera, R.; Hasse, B.; Sax, H.; Keller, P.M.
Summary: Background: A growing number of Mycobacterium chimaera infections after cardiosurgery have been reported by several countries. These potentially fatal infections were traced back to contaminated heater–cooler devices (HCDs), which use water as a heat transfer medium. Aerosolization of water contaminated with M. chimaera from HCDs enables airborne transmission to patients undergoing open chest surgery. Infection control teams test HCD water samples for mycobacterial growth to guide preventive measures. The detection limit of M. chimaera in water samples, however, has not previously been investigated. Aim: To determine the detection limit of M. chimaera in water samples using laboratory-based serial dilution tests. Methods: An M. chimaera strain representative of the international cardiosurgery-associated M. chimaera outbreak was used to generate a logarithmic dilution series. Two different water volumes, 50 and 1000 mL, were inoculated, and, after identical processing (centrifugation, decantation, and decontamination), seeded on mycobacteria growth indicator tube (MGIT) and Middlebrook 7H11 solid media. Findings: MGIT consistently showed a lower detection limit than 7H11 solid media, corresponding to a detection limit of ≥1.44 × 10 4  cfu/mL for 50 mL and ≥2.4 cfu/mL for 1000 mL water samples. Solid media failed to detect M. chimaera in 50 mL water samples. Conclusion: Depending on water volume and culture method, major differences exist in the detection limit of M. chimaera . In terms of sensitivity, 1000 mL water samples in MGIT media performed best. Our results have important implications for infection prevention and control strategies in mitigation of the M. chimaera outbreak and healthcare water safety in general.